Community nurses' attitudes, knowledge and educational needs in relation to urinary continence, continence assessment and management: A systematic review. Issue 7 (22nd July 2021) - McCann, Margaret; Kelly, Anne‐Marie; Eustace‐Cook, Jessica; Howlin, Claire; Daly, Louise
Abstract: Aims and objectives: To identify, appraise and summarise the available evidence relating to community nurses' attitudes, knowledge and educational needs in relation to urinary continence. Background: Community nurses play a pivotal role in identifying and supporting individuals who experience urinary continence issues. Gaps in nurses' continence‐related education and knowledge may contribute to sub‐optimal assessment and management across the continuum of care. Design: A systematic review. Methods: MEDLINE, CINAHL Complete and EMBASE were searched from inception to November 2020; keywords used included community nurses, urinary continence, incontinence, knowledge, attitude and education needs. Given the degree of heterogeneity between included studies, a meta‐analysis was not feasible. Included studies were critically evaluated; key study characteristics and findings pertinent to the review purpose were summarised. The review adhered to the PRISMA 2020 checklist. Results: Four studies reported in six papers were included. Community nurses lacked knowledge in certain areas of urinary continence and incontinence. Nurses reported they were adequately prepared but without sufficient knowledge to effectively care for those with urinary incontinence. Community nurses' attitudes to urinary incontinence were generally positive, but they demonstrated misconceptions that urinary incontinence was inevitable and less distressing for older people. Conclusions: There is limited research exploring community nurses' knowledge, attitudes and education needs in relation to urinary continence and incontinence care. Community nurses may have knowledge gaps and less favourable attitudes to some aspects of urinary continence care.